Nutraceutical Approach to Preventing Coronavirus Disease 2019 and Related Complications - Derosa, Giuseppe; Maffioli, Pamela; D’Angelo, Angela; Di Pierro, Francesco (Frontiers in Immunology, 2021)
Introduction Several months ago, Chinese authorities identified an atypical pneumonia in Wuhan city, province of Hubei (China) caused by a novel coronavirus (2019-nCoV or SARS-CoV-2). The WHO announced this new disease was to be known as “COVID-19”. Evidence Acquisition Several approaches are currently underway for the treatment of this disease, but a specific cure remains to be established. Evidence Synthesis This review will describe how the use of selected nutraceuticals could be helpful, in addition to pharmacological therapy, in preventing some COVID-19-related complications in infected patients. Conclusions Even if a specific and effective cure for COVID-19 still has some way to go, selected nutraceuticals could be helpful, in addition to pharmacological therapy, in preventing some COVID-19-related complications in infected patients.